Using hydro‐thermal time for assessing rice blast risk in subtropical Brazil. (26th June 2021) - Silva, Michel Rocha da; Streck, Nereu Augusto; Yang, Haishun; Ogoshi, Claudio; da Costa, Ivan Francisco Dressler; Rossato, Ioran Guedes; Pereira, Vladison Fogliato; Meus, Lorenzo Dalcin; Zanon, Alencar Junior
Abstract: In South Brazil, interannual variability leads to contrasting blast epidemics across years, varying from years when symptoms can barely be seen up to years with complete yield losses. To avoid yield losses, rice ( Oryza sativa L.) farmers apply more than two fungicide applications per rice growing season, even if weather conditions are not favorable for blast development. The objective in this study was to use accumulated hourly hydro‐thermal time (HTT) to assess interannual and regional weather variability for rice blast risk, using large data collected from multiple locations and years in southern Brazil. For each year × site × cultivar combination, HTT was calculated using hourly data of mean air temperature, relative humidity, and wind speed collected from weather stations. The HTT was correlated with blast onset to define a threshold for blast onset. The seasonal HTT between years × sites ranged from 5.1 to 725.3 °C h −1  year −1 . Blast risk started after accumulating HTT of 33.6, 66.8, and 75.6 °C h −1 from 1 June until rice emergence (EM) and after accumulating HTT of 12.5, 55.3, and 121.8 °C h −1 after EM for susceptible, medium‐resistant, and resistant rice cultivars, respectively. Our results strongly suggest that it is possible to improve fungicide management using the HTT approach over the calendar‐based approach, once we were able to discriminate the cultivar and year influence, the two most important factors on rice blast epidemics in southern Brazil. Core Ideas: Hydro‐thermal time is effective to quantify rice blast risk. Hydro‐thermal time ranged from 5.1 to 725.3 °C h −1 year −1 in Brazilian subtropics. Blast risk started after accumulating 12.5 °C h −1 for susceptible rice cultivars. Blast risk started after accumulating 121.8 °C h −1 for resistant rice cultivars.